Determinants of competitiveness of small and medium scale enterprises in the trading sector in Sub-Sahara Africa. (11th April 2022) - Asamoah, Emmanuel Selase; Doe, Frederick
This study examines the factors that determine the competitiveness of SMEs in the trading sector. The study highlights the internal and external factors, competitive strategies deployed by SMEs and measures to improve SMEs' competitiveness. The study ascertains the competitive strategies of SMEs in the trading sector and explores ways of enhancing the competitiveness of trading SMEs. The convenience sampling method was used to select a sample size of 450 SMEs from various markets in Accra, Ghana. The findings indicate management skills, capital, level of education and external relation management as the internal factors affecting SMEs competitiveness. On the other hand, it was revealed that, the external factors impeding SMEs competitiveness include, electricity supply, tax system, rent cost and consumer preference. Furthermore, there is no single strategy that an organisation can adopt to remain competitive in this highly dynamic market which has a relatively low barrier to entrants.